Analisa Studi Kelayakan Bisnis Yorigo Kohi Coffee shop Bandung - Ira Rachmawati Arsyady; Lilis Karnita Soleha (Universitas Widyatama, 2024)
The purpose of this research is to analyze whether Yorigo Kohi coffee shop can develop as expected by the owner, where this coffee shop is located in a residential area where there are no coffeeshops, there are rarely sellers, there are few offices. The menu sold by Yorigo Kohi Coffee shop tends to be like a coffee shop with cheap prices but with a contemporary touch, so that this coffee shop is quite busy being visited by young people who have just returned from school or college and workers who are just going to do assignments or have meetings. This research uses qualitative methods, where the data used comes from management, using literature studies, collecting information through several journals and sites on social media. The findings from this research are that, even though it has only been running for a few months, Yorigo Kohi Coffeeshop is quite promising to be developed The results of this research can also help develop theories about Micro, Small and Medium Enterprises (MSMEs) and entrepreneurship, especially for the coffee business, so that researchers can develop a framework for understanding small businesses. With practical implications, it can improve coffee shop businesses in identifying business opportunities, understanding customers, improving product and service quality, and can also help coffee shop owners in designing more effective marketing strategies. Keywords: Coffee, benefits of coffee, coffee shop business